Rapid screening of antibody–antigen binding using dynamic light scattering (DLS) and gold nanoparticles. Issue 17 (7th September 2015) - Lai, Yen H.; Koo, Sunghyu; Oh, Soon Hwan; Driskell, Elizabeth A.; Driskell, Jeremy D.
<x xml:space="preserve">Abstract</x> Antigen-mediated aggregation of antibody–gold nanoparticle conjugates is detected with dynamic light scattering to evaluate antibody–antigen binding.